The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1476-511x-12-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anti-inflammatory effects and high-density lipoprotein cholesterol levels between therapy with quadruple-dose rosuvastatin and rosuvastatin combined with ezetimibe

Abstract: BackgroundStatins are frequently administered to reduce low-density lipoprotein cholesterol (LDL-C) and vascular inflammation, because LDL-C and high sensitive C-reactive protein (hs-CRP) are associated with high risk for cardiovascular events. When statins do not reduce LDL-C to desired levels in high-risk patients with coronary artery disease (CAD), ezetimibe can be added or the statin dose can be increased. However, which strategy is more effective for treating patients with CAD has not been established. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
2
15
1
Order By: Relevance
“…The afore‐mentioned four studies had high risks of bias regarding allocation concealment , while the others had a lack of information on this aspect . Several studies showed a high risk of bias with respect to the blinding of participants, personnel and outcome assessors , and some contained insufficient information . Most of the included studies had a low risk of bias regarding incomplete outcome data, and only two exhibited a high risk of bias .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The afore‐mentioned four studies had high risks of bias regarding allocation concealment , while the others had a lack of information on this aspect . Several studies showed a high risk of bias with respect to the blinding of participants, personnel and outcome assessors , and some contained insufficient information . Most of the included studies had a low risk of bias regarding incomplete outcome data, and only two exhibited a high risk of bias .…”
Section: Resultsmentioning
confidence: 99%
“…The clinical trials used different doses of ezetimibe and statins. Two studies investigated ezetimibe 5 mg day –1 and 21 studies investigated ezetimibe 10 mg day –1 ; in regard to statins, one study investigated atorvastatin 5 mg day –1 , one study investigated atorvastatin 10 mg day –1 , two studies investigated atorvastatin 20 mg day –1 , two studies investigated atorvastatin 80 mg day –1 , one study investigated fluvastatin 30 mg day –1 , one study investigated lovastatin 5 mg day –1 , one study investigated lovastatin 20 mg day –1 , one study investigated rosuvastatin 2.5 mg day –1 , one study investigated rosuvastatin 10 mg day –1 , two studies investigated simvastatin 10 mg day –1 , one study investigated simvastatin 20 mg day –1 , seven studies investigated simvastatin 40 mg day –1 and two studies investigated simvastatin 80 mg day –1 . The range of intervention periods was from 2 weeks up to 12 months .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations